A Review through Therapeutic Attributes of Yashada bhasma - Chandran, Seetha (International Journal of Pharmaceutical & Biological Archive, 2017)
In Ayurveda, metal-based preparations are familiarly known as bhasmas. Yashada bhasma is one such bhasma. Textbooks of Ayurveda recommends Yashada bhasma (incinerated Zinc) as the treatment of choice in many diseases. Though bhasmas are being safely practiced in therapeutics in Indian scenario; concerns are being raised on safety issues in the recent past. So there is a necessity to assess and develop safety profile and to generate evidence. As a part of it, many research works are being carried out in various institutes of India. Five Postgraduate studies dealing with classical guidelines developing safety profile and therapeutic utilities of Yashada bhasma, carried out in Institute of postgraduate teaching and research in Ayurveda, Gujarat are selected for the present paper. Experimental Studies revealed that Yashada bhasma doesn’t have serious deleterious effect on body function as a whole. Clinical trials revealed its usefulness in Prameha (Diabetis mellitus), Swetapradara (Leucorrhoea) and Vicharchika (Eczema). No adverse effects were reported during the treatment period. Though certain limitations were observed, the results can be considered as a lead for further well stratified studies covering larger population.